Care to learn? The educational experiences of children and young people who are looked after - Alison Ritchie; Elizabeth Morrison; Steven Paterson (Scottish Journal of Residential Child Care)
In January 2002, the Scottish Executive commissioned a consortium of agencies to carry out the Learning with Care project. The aim of the project was to develop new materials to assist local authorities to improve educational outcomes for looked after and accommodated children and young people, and to implement the recommendations of the Learning with Care inspection report (Scottish Executive, 2001). Save the Children and Who Cares? Scotland worked with the BAAF Adoption & Fostering, the Scottish Institute for Residential Child Care, and the University of Strathclyde Department of Educational Support and Guidance, Professional Development Unit and Quality in Education Centre to develop the Learning with Care materials. These included a training pack (Hudson et al., 2003; and see Judy Furnivall and Barbara Hudson in this issue), an information booklet (Connelly et al., 2003), quality indicators [see Graham Connelly in this issue] and an education report which will form part of the Looking After Children in Scotland materials.